FLEXIBILITY OF BUDGET ACCOUNTABILITY USING FLOW MODIFICATION IN THE DESIGN OF VILLAGE FINANCIAL ACCOUNTING - Dasmi Husin (Association of Certified Fraud Examiners Indonesia Chapter, 2016)
This study aims to find out the implementation of government regulations contained in Law No. 6 of 2014 on the village and the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 113 of 2014 on guidelines for the management of village finances. The research was conducted in 10 villages in Lhokseumawe Municipality and North Aceh Regency. Research method was conducted by comparing between the financial format provided by the government and the realization of financial accounting implementation in the villages. The research findings indicate that many village officials cannot record and report the use of village budget because of the complexity of the procedure and the limited understanding on the forms provided. To overcome these problems, it is necessary to be modifying the flowchart of financial accounting by way of revising little village book format. The aim is to make the village officials able to prepare the financial accountability properly. The flow modification in the design of village financial accounting should meet the principles of flexibility without abandoning the existing government accounting standards. The design includes village bankbooks, general book, direct expenditure book, and indirect expenditure book, Village Budget (APBDes) and Budget Realization Report (LRA). This design is believed to be able to provide a solution to the problem of financial management accountability in the village. These findings are an excellent lesson on the village financial management in Aceh Province, Indonesia.